Multiple-cause coding of death from myocardial infarction: population-based study of trends in death certificate data. - Goldacre, M; Roberts, SE; Griffith, M (2003)
BACKGROUND: Data on long-term trends in mortality are generally unavailable for multiple-cause coding of deaths. We wanted to know whether multiple-cause coding of deaths for myocardial infarction contributes much to the interpretation of death certificate data on mortality rates for this condition. METHODS: We analysed all causes of death on death certificates in the former Oxford health service region from 1979 to 1998. RESULTS: Of 69,333 death certificates that included myocardial infarction as a cause of death, it was the underlying cause of death in 93.6 per cent. The ratio of 'mentions' to 'underlying cause' was broadly similar over the study period, during which time there were substantial falls in mortality rates. There were significant changes to the ratios, associated with timing of changes to coding rules; but their effects were small. The ratio of mentions to underlying cause was similar in men and women and in different age groups. CONCLUSION: The underlying cause of death was a robust and almost complete measure of certified deaths for myocardial infarction.